Microfluidic Single‐Cell Analysis with Affinity Beads. Issue 22 (29th January 2015) - Werner, Michael; Palankar, Raghavendra; Arm, Loïc; Hovius, Ruud; Vogel, Horst
<x xml:space="preserve">Abstract</x> A micrometer‐sized affinity bead (red) is (i) taken up into a cell by phagocytosis, (ii) photochemically released from phagosomes, (iii) optically trapped by the cell, and (iv) isolated by cell lysis for subsequent analysis of captured intracellular analyte (green).